Immigrant integration and policy framework : an analysis on the impact of integration policies of immigrants within Finland and their economic influence within the welfare state - Mwacharo, Salome Safo (2018)
The purpose of this thesis is to find out how the implementation of immigrant integration policies have affected immigrants and whether in turn, this has had an effect within the Finnish economic sector. This paper will specifically focus on the decision making processes behind immigrant integration policies, highlighting its different scopes, efficiency as well as the different roles the various actors play and contribute to shaping these policies. Historically, the issue of immigration was a crucial concern throughout Europe which ultimately brought about high demand for labour, meaning Europe was in desperate need of a high number of qualified immigrants. However, in recent times, there has been a shift and influx of refugee immigration, which brought about significant challenges including the need to integrate these immigrants into their new host societies. This influx of immigration resulted in prohibitive policies at the macro and micro level i.e. European Union level and National level, making it difficult for successful integration measures to take place. This, in turn, affected the labour market and put a strain on the welfare state because there was a high number of unskilled labour and high demand for social assistance. Through the analysis of case studies, government records, EU portals and network portals as well as policy journals, the study concluded that the chain of immigrants coming into to the EU and specifically into Finland are mostly highly skilled and educated individuals from war-torn countries seeking asylum, followed closely by economic immigrants who come into the country seeking better jobs and improved standards of living. They manage to successfully retain their original cultures while at the same time engaging themselves with their new cultures thus successfully being integrated into the Finnish society. This, in turn, has a positive effect on the Finish labour market in that due to their high levels of education, they are able to work and pay their taxes which in turn alleviates the pressures placed on the welfare system. However, there was also some shortcomings that emerged which highlighted the importance of an effective EU strategy which stretches beyond the regulation of minimum legal principles and sharing of information to promote the integration of immigrants.